Recent Progress in the Synthetic Assembly of 2-Cyclopentenones - Aitken, David J.; Eijsberg, Hendrik; Frongia, Angelo; Ollivier, Jean; Piras, Pier Paolo (Synthesis, 2014)
An overview of the most important synthetic strategies currently available for the preparation of cyclopent-2-enones is presented and illustrated with recent applications.1 Introduction2 Multicomponent Ring Assembly3 Cyclizations4 Transformations of Existing Cyclic Systems5 Miscellaneous Methods6 Conclusions
Keywords: cyclopentenones; cyclization; carbocycles; ring closure; rearrangement; annulation